Integration of grid array antenna with Dye Sensitised Solar Cell (DSSC) - Nur Izzati Mohd Ali,; Norbahiah Misran,; Mohd Fais Mansor,; Norsuzlin Mohd Sahar,; Mohd Faizal Jamlos,; Eryana Eiyda Hussin, (Penerbit Universiti Kebangsaan Malaysia, 2024)
Wireless communication systems require electrical energy to operate and function. Whereas standalone applications require reliable power sources which can be realised by photovoltaic technology. Typically, photovoltaic cells and antennas are two separate devices. These devices compete for space in mobile or standalone systems, where available space is generally very limited. To address this issue, a combination of an antenna and a solar cell into a single device is needed. Integrating an antenna with a solar cell is challenging due to the importance of maintaining a compact, simple design while achieving optimal efficiency for both elements. This study focuses on designing a transparent grid array antenna integrated with Dye-Sensitized Solar Cells (DSSC) for Ku-band applications. The grid array design aims to improve antenna performance and is chosen for its suitability with the design and structure of the solar antenna device. The integrated antenna and solar cell were simulated using Computer Simulation Technology (CST) software at a frequency of 14 GHz for Ku-band applications. A prototype of the antenna and solar cell was fabricated, then tested and measured for the efficiency of both the antenna and solar elements. For the solar element, performance measurements were conducted using a halide lamp to mimic sunlight, with results presented in the form of current-voltage curves. In summary, by the end of this study, a transparent solar antenna for Ku-band applications was successfully designed with a gain exceeding 10 dBi. The solar cell’s performance showed an open-circuit voltage (VOC) of 0.6733 V, a short-circuit current density (JSC) of 2.06 mA/cm², a fill factor (fF) of 29.31%, and a power conversion efficiency (η) of 0.407%.